2016
DOI: 10.1007/s10461-016-1569-5
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Health Information Seeking, Processing, and Use Among HIV Positive Adults in the Dominican Republic

Abstract: Effective treatment and management of human immunodeficiency virus (HIV) depend on patients’ ability to locate, comprehend, and apply health information. This study’s purpose was to identify characteristics associated with these skills among HIV positive adults in the Dominican Republic. An information behavior survey was administered to 107 participants then three logistic regressions were conducted to identify characteristics associated with information seeking, processing, and use. Never having cared for so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 67 publications
2
9
0
Order By: Relevance
“…As previously reported (Stonbraker, Befus, et al, 2016; Stonbraker, Castillo, et al, 2016), the average age of participants ( N = 107) was 40.8 years (range = 19 – 75) with an average time living with HIV of 7.7 years (range = 0.17 – 20). The majority of participants self-identified as heterosexual (88.7%), 2.8% indicated they were men who have sex with men, 2.8% were bisexual, 1.8% were transgender women who have sex with men, and 3.7% reported that they were no longer sexually active.…”
Section: Resultssupporting
confidence: 65%
See 1 more Smart Citation
“…As previously reported (Stonbraker, Befus, et al, 2016; Stonbraker, Castillo, et al, 2016), the average age of participants ( N = 107) was 40.8 years (range = 19 – 75) with an average time living with HIV of 7.7 years (range = 0.17 – 20). The majority of participants self-identified as heterosexual (88.7%), 2.8% indicated they were men who have sex with men, 2.8% were bisexual, 1.8% were transgender women who have sex with men, and 3.7% reported that they were no longer sexually active.…”
Section: Resultssupporting
confidence: 65%
“…This brief research report focuses on a single item from a larger study about the health information behaviors of PLWH, the results of which are reported elsewhere (Stonbraker, Befus, Lerebours Nadal, Halpern, & Larson, 2016; Stonbraker, Castillo, et al, 2016). During survey administration, we asked the question, What things do you want your friends, family, or members of the community to know about HIV?, with the additional prompt, Could you please tell me two things that you wish the rest of the world knew about HIV?…”
Section: Methodsmentioning
confidence: 99%
“…Health literacy is regarded as a key factor for improving population health (WHO, ) and it indicates the ability to obtain, appraise and understand health information (Nutbeam, ; Sillence et al., ; Sørensen et al., ; Stonbraker et al., ). As a future service provider for medical and health systems, nursing students will act as a “bridge” between patients and doctors in patients’ health education and health promotion activities.…”
Section: Discussionmentioning
confidence: 99%
“…It is regarded by the World Health Organization (WHO) (2009) as a key factor for improving population health. The definition of health literacy not only implies the ability of a person to obtain and understand health information but also includes the ability to appraise and use health information to make appropriate health-related decisions (Nutbeam, 2008;Sillence, Briggs, Harris, & Fishwick, 2007;Sørensen et al, 2012;Stonbraker, Befus, Nadal, Halpern, & Larson, 2016). Furthermore, the effect of health literacy on health outcomes begins with the ability to obtain information (Shieh, Mays, Mcdaniel, & Yu, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, information needs may vary depending on age or gender, or among high‐risk groups (Stonbraker & Larson, ). For instance, in the DR, despite similar HIV prevalence rates among men and women, men are more likely to report higher‐risk sexual behaviors than women (Curtis & Sutherland, ) and are more likely to be active information seekers (Stonbraker, Befus, Lerebours Nadal, Halpern, & Larson, ). This is important to consider in a cultural context where heterosexual transmission of HIV between stable partners is common (Jimenez, Andrade, Raffaelli, & Iwelunmor, ).…”
Section: Discussionmentioning
confidence: 99%